ChemInform Abstract: Recent Advances in Solid State NMR of Small Molecules in Confinement. Issue 19 (13th May 2014) - Werner, Mayke; Rothermel, Niels; Breitzke, Hergen; Gutmann, Torsten; Buntkowsky, Gerd
Abstract Review: 121 refs.